In Vitro, Ex Vivo, and In Vivo Evaluation of Nanoparticle-Based Topical Formulation Against Candida albicans Infection - Sajid Khan Sadozai; Saeed Ahmad Khan; Abdul Baseer; Rooh Ullah; Alam Zeb; Marc Schneider (Frontiers Media S.A., 2022)
Ketoconazole is commonly used in the treatment of topical fungal infections. The therapy requires frequent application for several weeks. Systemic side effects, allergic reactions, and prolonged treatment are often associated with non-compliance and therapy failure. Hence, we developed an optimized topical antifungal gel that can prolong the release of drug, reduce systemic absorption, enhance its therapeutic effect, and improve patient compliance. Ketoconazole-loaded PLGA nanoparticles were prepared by the emulsion/solvent evaporation method and were characterized with respect to colloidal properties, surface morphology, and drug entrapment efficiency. The optimized ketoconazole-loaded PLGA nanoparticles and commercially available silver nanoparticles were incorporated into a Carbopol 934P-NF gel base. This arrangement was characterized and compared with commercially available 2% ketoconazole cream to assess physical characteristics of the gel, in vitro drug release, ex vivo skin permeation and retention, and in vivo studies on Wister male albino rats. The results showed that polymeric PLGA nanoparticles were very effective in extending the release of ketoconazole in our optimized formulation. Nanoparticles were smooth, spherical in shape, and below 200 nm in size which is consistent with the data obtained from light scattering and SEM images. The ex vivo data showed that our gel formulation could strongly reduce drug permeation through the skin, and more than 60% of the drug was retained on the upper surface of the skin in contrast to 38.42% of the commercial cream. The in vivo studies showed that gel formulation could effectively treat the infection. This study demonstrates that our topical gel could be effective in sustaining the release of drug and suggests its potential use as a possible strategy to combat antifungal-resistant Candida albicans.